Do voluntary payments to advisors improve the quality of financial advice? An experimental sender-receiver game - Vera Angelova; Tobias Regner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
The market for retail financial products (e.g. investment funds or insurances) is marred by information asymmetries. Clients are not well informed about the quality of these products. They have to rely on the recommendations of advisors. Incentives of advisors and clients may not be aligned, when fees are used by financial institutions to steer advice. We experimentally investigate whether voluntary contract components can reduce the conflict of interest and increase truth telling of advisors. We compare a voluntary payment upfront, an obligatory payment upfront, a voluntary bonus afterwards, and a three-stage design with a voluntary payment upfront and a bonus after. Across treatments, there is significantly more truthful advice when both clients and advisors have opportunities to reciprocate. Within treatments, the frequency of truthful advice is significantly higher when the voluntary payment is large.
Keywords: C91; D03; D82; G20; L15; M52; 330; financial advisors; asymmetric information; principal-agent; sender-receiver game; reciprocity; experiments; voluntary payment; Anlageberatung; Honorar; Kapitalanlage; Asymmetrische Information; Informationsverhalten; Austauschtheorie (Soziologie); Spieltheorie; Test